Investigation of Isolated Blastocystis Subtypes from Cancer Patients in Turkey - Mulayim, Sefa; Aykur, Mehmet; Dagci, Hande; Dalkilic, Semih; Aksoy, Asude; Kaplan, Mustafa (Springer Int Publ Ag, 2021)
Purpose It is not clear that Blastocystis remains without damage to the digestive tract or has a pathogenic effect in relation to subtypes in immunocompromised people, such as cancer patients. The present study aimed to investigate the frequency and subtype distribution of Blastocystis in cancer patients who were followed-up and treated in the Oncology clinic of Firat University Hospital and to determine the clinical signs of infected sufferers. Methods 201 patients aged >= 18 with a diagnosis of cancer were enrolled in this cross-sectional study. Patients' stool samples were examined between September 2017 and August 2019 by native-Lugol, trichrome staining. Microscopy-positive stool samples were subjected to DNA isolation and subtyped by Sequence Tagged Site (STS)-PCR analysis. The symptoms and demographic characteristics of the patients were also evaluated. Results Totally, 29 (14.4%) samples were positive for Blastocystis after all methods. 15 (51.7%) out of 29 samples were successfully subtyped by the sequenced-tagged site(STS)-PCR, while 14 (48.3%) could not be typed. Three subtypes of Blastocystis were detected: ST3 (40%), ST2 (33%), ST1 (20%), and one mixed infections with ST1/ST2 (6%). There was no statistically significant difference in terms of clinical findings and demographic characteristics. Conclusion The outcomes of our study promote the idea that Blastocystis could be an asymptomatic and harmless commensal organism. However, more comprehensive molecular and clinical studies are needed to fully determine the pathogenicity and epidemiology of Blastocystis in cancer patients.
Keywords: Blastocystis; Cancer; Immunocompromised; Subtype; Turkey